Moralni pragmatizem pri etičnem odločanju managerjev - Drašček, Matej (Družboslovne razprave, 2020)
The ethical decision-making of managers based on ethical approaches has not been yet researched in Slovenia. The purpose of the study was to find out which basic normative ethical approaches managers use in different circumstances and which personal and organizational variables influence their choices. Moreover, the virtue ethics is included as a normative ethical approach, not as an independent variable. Based on analysis of vignettes among a sample of 166 managers, the research shows that in personal and business life virtue ethics is the dominant ethical approach, while deontology is the prevailing one for general ethical dilemmas. Only a limited number of independent variables influence managers' choice of ethical approach. We conclude that moral pragmatism is the answer for the ethical decision-making of managers.
Keywords: Decision making; deontolodgija; Ethics; Etika; Managerji; Managers; Odločanje; Pragmatism; Pragmatizem; Utilitarianism; Utilitarizem